Editorial (Thematic Issue: Synthesis, Characterization and New Applications Of Catalytic Materials) - Briand, Laura; Romanelli, Gustavo (Current Catalysis, 2014)
Our research Center called “Centro de Investigación y Desarrollo en Ciencias Aplicadas - Dr. Jorge Ronco, CINDECA” celebrated 40 years of its foundation. Our research Institute is devoted to heterogeneous and homogeneous catalysis, reactors design, green chemistry, bio-catalysis, design and synthesis of new catalytic materials between others. In this context, the research topics are oriented towards the technological application in the field of catalyzed chemical processes. Our research Center organized a series of events such as invited conferences from worldwide researchers and poster sessions. In fact, 150 participants mostly P.h.D students along with researchers from all over Argentina gathered for three days to discuss their research and debate new and exciting ideas. In the present special issue eighteen manuscripts on different subtopics such as, new synthetic material, homogeneous catalysis heterogeneous catalysis, bio-catalysis, green chemistry, organic clean procedures and environmental remediation have been subjected to consideration. I would like to take this opportunity to thank Bentham Science Publishers for appointing us as Editor-in-Chief of the journal, and to acknowledge supporting staff for their enthusiasm, dedication and continual support. I also thank authors and reviewers for their positive contribution and wish the journal will have a great success.